Dakwah Melalui Podcast: Nilai – Nilai Agamis Generasi-Z Di Era Digital - Mujahidin, Irfan; Sobar, Amin; Marjuki, Marjuki; Akbariyah , Siti; Gito, Gito (STAI Publisistik Thawalib Jakarta, 2024)
Community service is carried out with the aim of preaching religious values ??to generation-Z in the digital era. Da'wah is carried out using podcast media at the Ash-Shomad mosque in Banten. The results of the dedication show that da'wah through podcast media runs well and smoothly. Material about the importance of religious values ??in generation-Z in the digital era has been conveyed well by the implementers. These values ??are ethics, morals, social relationships, the importance of personal character, self-control, social ethics and so on.